AN INDONESIAN PERSPECTIVE TOWARD MARITIME VISION: IS PURSUING NATIONAL INTEREST WHILE MAINTAINING NEUTRALITY IN THE SOUTH CHINA SEA POSSIBLE? - Ramadhani, Masyithoh-Annisa (European Scientific Journal, ESJ, 2015)
Overlapping claims in the South China Sea has turned into a contested zone for global powers to project their roles in the region. Given the political uncertainty in international affairs, states prefer to acquire their own national interests for the sake of nations’ prosperity. Indonesia, one of regions’ prominent actors committed to be a non-claimant state in the dispute, is trying to invigorate cooperation through its maritime vision notably known as ‘’Global Maritime Nexus’’ despite region’s security dilemma. It aims to enhance mutual opportunities for all actors involved at the dispute thereby diminishing any possibility of the worsening power competition. Association of the Southeast Asian Nations (ASEAN) as one of regions’ most prominent multilateral organizations is expected to be a cornerstone for a more peaceful dispute settlement so it could move forward on fostering members’ prosperity and security. However, Indonesia is a sovereign state which must hold their national interests at stake when it comes to any international affairs. It is therefore becoming a challenge for Indonesia on pursuing national interests while maintaining its neutral position as non-claimant state at the same time.